Seeing Each Other Clearly: A Dual Perspective on Providing Healthcare to Neurodivergent People - Kelly, Clive; Downs, James (British Journal of Healthcare and Medical Research, 2026)
Neurodivergent people face distinctive challenges in Health Care, where environments, routines, and communication styles are often poorly attuned to their needs. This paper, written jointly by a neurotypical physician and a neurodivergent patient, offers unique perspectives on how these dynamics can generate misattunement and mistrust. Drawing on reflective narrative accounts and their analysis through the concepts of epistemic injustice and double empathy issues, the paper shows how behaviours such as silence, detailed explanation, or avoidance of eye contact are easily misinterpreted. Patients may be disbelieved or blamed, while clinicians, under systemic pressures of time and workload, may resort to defensive practices. Addressing these challenges requires valuing difference, adapting responsively, and fostering inclusive communication, supported by system-level reforms that embed co-production, training, and accessible environments. We demonstrate how this can be achieved in clinical practice to the mutual benefit of both neurodivergent people and those who care for them.